Association schemes based on subspaces in singular unitary spaces - Guo, Jim (Utilitas Mathematica, 2018)
Let + be the (2i/+1 +£)dimensional singular unitary space over the finite field Fqi. In this paper, we construct an association scheme by using subspaces of type (1/ + lf 1,0) in and com pute its intersection numbers. A MS classification: 05E30, 05B25. © 2018 Utilitas Mathematica Publishing Incorporated. All rights reserved.